Long-term motor and sensory outcomes after surgery for infantile esotropia - Altınsoy, Halil Ibrahim; Gokce, Gokcen; Ceylan, Osman Melih; Mutlu, Fatih Mehmet (Vojnosanitetski pregled, 2017)
Background/Aim. Infantile esotropia (ET), entitled as congenital ET, is defined as an alternating, cross-fixational ET that occurs within the first 6 months of life. The aim of this study was to determine the long-term motor and sensory outcomes after surgical correction of patients with infantile ET. Methods. Medical records of 108 consecutive children who had bimedial rectus recession (BMR) initially for ET were reviewed retrospectively. The patients were divided into 3 groups: the group I, surgery before one-year old; the group II, surgery between one and two-year old; the group III, surgery after two-year old. Results. No significant differences were determined among the groups for preoperative mean angle of deviation and refractive error (p > 0.05, for both). Development rate of dissociated vertical deviation (DVD) was greater (40%) in the group I, and the relationship between the rate of DVD and the timing of the initial surgery was statistically significant (p = 0.03). Risk for additional surgery was significantly greater in patients with a younger mean age at initial surgery (p = 0.01). Although measurable stereopsis rate was higher in the group I (35%, 32.4%, 27.8%, respectively) the difference among the groups was insignificant (p = 0.80). Conclusion. Patients with ET have limited potential of high grade stereoacuity despite the early alignment of eyes. Early surgery also has potential effects for the development of both inferior oblique overaction and DVD earlier.